The Effect of Bending Strength of Concrete Using Machine Crushed Fine Aggregate - Enita Suardi; Mukhlis; Oni Guspari; Illona Giovanni; Ila Putri Yani (International ABEC, 2022)
Concrete is a mixture of Portland cement or other hydraulic cement, fine aggregate, coarse aggregate, and water with or without additives to form a solid mass. Cement concrete pavement is a pavement construction with aggregate as raw material and uses cement as a binding material, so it has a relatively high level of rigidity, especially when compared to asphalt pavement. The fine aggregate commonly used is natural fine aggregate. Due to the increasing use of fine aggregate in construction so as to obtain the fine aggregate by means of sand mining, ecological damage in some areas. Therefore, the use of natural fine aggregate can be replaced with machine crushed aggregate. Based on this, this study aims to determine the maximum compressive strength of concrete, maximum flexural strength of concrete blocks using a mixture of machined aggregate percentage. The research method was carried out with 15cm x 15cm x 60cm beams. Variation of the test specimen mixture is a mixture that meets the maximum combined gradation limit of 30mm. Flexural strength testing was carried out at the age of 56 days. The highest flexural strength test results are found in variation 2, which is 4.85 MPa.